2009
DOI: 10.1016/j.surneu.2008.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Observation of the embolus protection filter for carotid artery stenting

Abstract: Background: Carotid artery stenting (CAS) in high-surgical-risk patients is considered

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 16 publications
(14 reference statements)
2
7
0
Order By: Relevance
“…The method was simple and required no special instrument. The debris was observed on the filter and the finding was consistent with preoperative imaging studies [4]. In this study, we revealed the function of the AG and FW, and evaluated the cause of the intraoperative flow impairment.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…The method was simple and required no special instrument. The debris was observed on the filter and the finding was consistent with preoperative imaging studies [4]. In this study, we revealed the function of the AG and FW, and evaluated the cause of the intraoperative flow impairment.…”
Section: Discussionsupporting
confidence: 77%
“…We developed a debris observation method staining with HE [3,4]. The method was simple and required no special instrument.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7] The observation that normal antegrade flow is restored in all patients with slow flow after filter retrieval strongly suggests that the occlusion of the pores in the filter membrane is responsible for the impaired antegrade flow. [1][2][3][4][5][6][7] Flow impairment, which has been associated with periprocedural ischemic events, 1,2 is thought to cause blood to stagnate just proximal to the filter, leaving debris floating in the proximal ICA column. This consequence of flow impairment requires the use of an aspiration catheter to remove blood in the ICA just proximal to the filter before it is retrieved.…”
mentioning
confidence: 99%
“…Until recently, the evaluation of the burden of embolic debris has been dependent upon visual inspection or performed using optical microscopy (Angelini et al, 2002;Rogers et al, 2004;Quan et al, 2005;Hayashi et al, 2009) or electron microscopy (DeRubertis et al, 2007;Brightwell et al, 2011). However, optical and electron microscopy require multiple steps of staining and thin-slice dissection.…”
Section: )mentioning
confidence: 99%